STRATEGI PENYELESAIAN MASALAH MENGGUNAKAN KOPING DENGAN BURNOUT PADA PERAWAT: Literature Review - Januarita Akhrina (2020)
Nurses as providers of nursing care have high responsibilities so they are very vulnerable to burnout. Burnout can be overcome by strategies for solving problem using coping with burnout. The purpose of this literature review is to analyze coping strategies that are used by nurses to deal with and overcome burnout while working. This literature review method uses PRISMA flow taken from Scopus, Pubmed, Ebsco, Science Direct, and Sage databases using English in the last 5 years. The search terms included in the keywords are "nurse", "coping strategies" and "burnout". The study results obtained through two methods of screening using the PICO formula and CRAAP method were 6 studies. The factors that can influence burnout are length of work experience, coping styles, personality, and social support which can have an impact on physical health, mental health, workplace, quality of care and conditions of recovery of patients. Problem solving strategies using coping can overcome burnout in nurses. Early detection of burnout symptoms and training on problem solving strategies using coping need to be made by hospital nursing management to monitor the burnout status of nurses and nurses' readiness in overcoming burnout.